O ecodesign e sua contribuição no processo de encaixe do vestuário jeans - Souza, Josiane Gonçalves de (2014)
This paper aims to explain the importance of effective development in an industry of making jeans with active methods to develop ways to use the raw material with principles concerning the prevention of pollution by means of processes allied to the Eco Design. In developing a Cleaner Production (CP) that seeks to minimize the generation of waste and pollutants in its source and in the production process, helping the environmental performance through appropriate techniques from a rereading and interpretation that modeling allows flat, an essential step and certain procedures to be established, enabling the necessary resources for the development of sustainable products with quality, product planning and environmental awareness.